1998
DOI: 10.1590/s0100-879x1998000900004
|View full text |Cite
|
Sign up to set email alerts
|

A single-step purification of bothropstoxin-1

Abstract: Bothrops venoms are complex mixtures of components with a wide range of biological activities. Among these substances, myotoxins have been investigated by several groups. Bothropstoxin-1 (Bthtx-1) is a phospholipase A 2 -like basic myotoxin from Bothrops jararacussu. The purification of this component involves two chromatographic steps. Although providing a pure material, the association of these two steps is time consuming and a single-step method using high performance chromatography media would be useful. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
(11 reference statements)
0
4
0
2
Order By: Relevance
“…Similarly to other Lys49-PLA2s, such as PrTx-I, PrTx-II [25] and BthTx-I [21], BjVIII does not show significant enzymatic activity and induces similar myonecrosis as BthTx-I, when assayed at the same conditions as Barbosa et al [26]. However, an atypical effect presented by BjVIII, and not by other Lys49-PLA2s, is a strong human platelet aggregation activity.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Similarly to other Lys49-PLA2s, such as PrTx-I, PrTx-II [25] and BthTx-I [21], BjVIII does not show significant enzymatic activity and induces similar myonecrosis as BthTx-I, when assayed at the same conditions as Barbosa et al [26]. However, an atypical effect presented by BjVIII, and not by other Lys49-PLA2s, is a strong human platelet aggregation activity.…”
Section: Resultsmentioning
confidence: 70%
“…Bothrops toxin I (BthTx-I) was the only Lys49-PLA2 purified from Bothrops jaracussu venom by one chromatographic step [21]. We modified the original protocol, using a two-step chromatographic procedure (section Materials and methods ) and observed that BthTx-I fraction from the one-step protocol is composed of two closely related isoforms.…”
Section: Resultsmentioning
confidence: 99%
“…Spencer et al [31] described the purification of BthTX-I with the use of Resourse S® (methyl-sulphonate Ion-exchange chromatography on CM-Sephadex® column.…”
Section: Bothrops Moojenimentioning
confidence: 99%
“…The column was subsequently washed with 10 mL of B buffer, followed by 10 mL of A buffer to wash NaCl out of the column (13). …”
Section: Bothropstoxin-1 Purificationmentioning
confidence: 99%